Ethanol as a Husehold Fuel in Madagascar : Health Benefits, Economic Assessment, and Review of African Lessons for Scaling-up - World Bank (Washington, DC, 2013)
This study was commissioned to analyse the cost efficiency and economic viability of an ethanol programme, for reducing disease, and protecting the forests in Madagascar. This information is also expected to be of interest regionally and internationally, given that the World Health Organization (WHO) estimates that there are nearly two million deaths per annum globally due to Household Air Pollution (HAP), representing 2.7 percent of the global burden of disease. Of these, nearly 400,000 deaths per annum due to HAP, are in sub-Saharan Africa. With only 20 percent of the world's population, Africa suffers a disproportionate share of around half of all deaths from pneumonia for children under five years, for which HAP is a major risk factor. This study investigates the potential of ethanol as a household fuel in Madagascar, focusing on three main components: health benefits, financial and economic assessment, and African lessons for scaling-up a program of support for ethanol as a household fuel.